The Importance of Competency Approaches in Teaching Mathematics in Secondary Schools - Sariyeva E’tibor Matchanboyevna (Genius Journals, 2023)
This article shows the importance of the competence approach in teaching mathematics and the importance of creating interest in the subject in the students
Keywords: Mathematics; competence; approach